MEMÓRIAS SOBRE A CAFEICULTURA E A GEADA NEGRA DE 1975 EM SÃO PEDRO DO IVAÍ- PR, 1970-2018 - Santos, Eliane Aparecida Miranda Gomes dos (2019)
Coffee growing has played an important role in the Brazilian economy, especially in the state of Paraná. In 1950, the state was considered the largest coffee producer. Therefore, through coffee growing, several municipalities were formed in the north of the state and, in this context, São Pedro do Ivaí. The frequent frosts that occur in the state prevented the development of the coffee crop, especially the 1975 black frost, which caused major changes in the coffee growing scenario. In the memory of many inhabitants of the city, this frost is considered responsible for the end of coffee cultivation in the municipality. This dissertation, entitled “Memories of Coffee growing and Black Frost 1975 in São Pedro do Ivaí-Pr, 1970-2018”, sought to analyze, through interviews with former residents, the collective memory about experiences and perceptions about the reality experienced in the period of decline and extinction of coffee growing in the municipality and the impacts of black frost on that social reality, privileging, above all, the memories of social subjects often excluded from the history of São Pedro do Ivaí, such as women, children and adolescents. The black frost of 1975 dealt a coup de grace to coffee farmers to make the final decision to leave the farm, as the modernization of agriculture was already knocking on the state's door.